Remodelling of skeletal tissues bone and structural specialisations in an elasmosaurid (Sauropterygia: Plesiosauroidea) from the Upper Cretaceous of Patagonia, Argentina - Talevi, Marianella (2015)
Fil: Talevi, Marianella. Universidad Nacional de Río Negro. Instituto de Investigación en Paleobiología y Geología. Río Negro, Argentina.